Process Capability Analysis for Quality Control at the Mixing Stage of Animal Feed Products at PT. Gold Coin Indonesia - Ari Astalita Madiana (International Journal of Mechanical Computational and Manufacturing Research, 2022)
Gold Coin Indonesia is one of the companies engaged in the processing of poultry feed, namely chicken, duck, quail, pig feed and fish feed. The products produced by this company consist of several types including crumble, layer, pellet and concentrate. The main problem discussed in this study is that there are still 201 C animal feed products (broiler starter) produced that do not meet the quality standard specifications set by the company, so concrete steps need to be taken so that the resulting quality can be achieved. The step taken is the process capability technique to see how far the process capability in producing the product is in accordance with the desired specifications. The data used in this study were the percentage of protein content, fat content, water content, ash content, calcium content and phosphorus content of animal feed products 201 C (broiler starter) to determine process capability by looking at the Cp and Cpk values. Based on the results of research conducted using process control techniques with control charts obtained control limits for each characteristic and the presence of data outside the control limits caused by general and special variations. Process Capability (Cp) has a value of less than 1 (Cp < 1) which means that the process is not good enough to meet the specifications so that its performance needs to be improved through improving the process itself. For water content (Cpk = 1.7202), ash content (Cpk = 3.3806), fat content (Cpk = 1.210) the Kane Performance Index (Cpk) > 1 and for protein content (Cpk = 0.5013), the levels of calcium (Cpk=0.998) and phosphorus content (Cpk=0, that the process is not good in meeting the specifications that have been set.